Public education during epidemics of infectious diseases: A national mixed-method study with parallel convergent design in a low and middle-income country - Saber Azami-Aghdash; Salar Mohammaddokht; Maryam kashani; Nima Pourgholam; Mohsen Nouri; Elaheh Nasiri (PLoS ONE, 2025)
Introduction Proper and effective public education during epidemics of infectious diseases can have a key effect in controlling epidemics and reducing their complications. Therefore, the present study aims to assess public education methods during infectious disease epidemics from the perspectives of both the public and experts in Iran. Method The present study is a mixed-methods (quantitative-qualitative) with a parallel convergent design conducted in 2024 in Iran. The public’s views on the effectiveness, strengths, and weaknesses of each method used for educating people during epidemics, with a focus on the COVID-19 epidemic, were collected through a self-development valid and reliable questionnaire (with closed and open-ended questions). Quantitative data was analyzed using SPSS:16 software. In the qualitative section, data were collected by semi-structured interviews and manually analyzed using content analysis methods. Results Television (79.9%), social networks (78.8%), and websites (78.5%) were introduced as sources that have performed best, provided various information and education, had a high impact on the audience, and successfully gained people’s trust during epidemics of infectious diseases. In the qualitative section, the majority of participants identified in-person training as the most effective method of educating people. Utilizing the capacities of mass media and providing accurate information to the public were strengths, while dissemination of false and unscientific information and lack of trust in relevant institutions were identified as weaknesses in educating people during epidemics of infectious diseases. Conclusion In this study, an attempt was made to provide comprehensive and sufficient information for decision-making and effective planning for public education in the next epidemics of infectious diseases.